The Pervasive Influence of Shipping Culture in K-pop and Its Impact on Gender Dynamics - Yuan, Keyi (Transactions on Social Science, Education and Humanities Research, 2024)
Among the KPOP culture, it involves different fan activities for example music, dancing. This article discusses the relationship between shipping couple culture and gender issues. The shipping couple culture refers to the phenomenon of being enthusiastic about combining two or more fictional characters into a romantic relationship. This article analyzes the background, characteristics, and influence of this culture, and explores its interaction with gender issues. Firstly, the article discusses the impact of the couple culture on gender expression and identity. Secondly, this article explores the potential of this type of culture in creating new gender models and shaping gender equality concepts. Then, this article analyzes the gender stereotypes and binary oppositions in the culture of drug abuse, as well as the limitations and challenges to gender diversity and inclusivity. Finally, the article points out the significant impact of the interaction between shipping couple culture and gender issues on individuals and society and proposes some future research directions.